COMPARATIVE CHARACTERISTICS OF THE EFFECTIVENESS OF DIRECT AND INDIRECT RESTORATIONS ON TEETH WITH DISCOLORATION - I.V. Zhyvotovskyi; Yu.I. Sylenko; M.V. Khrebor (Український стоматологічний альманах)
The rapid development of dental industry and constant improvement of technologies in production of basic dental materials contribute to the increase of the quality of rendering dental care with the obligatory consideration not only of functional but also aesthetic parameters during a patient's rehabilitation. However, there is still no precise indication for the use of metal-free structures for the qualitative and durable aesthetic restoration of the frontal group of teeth, white-pink aesthetics and prosthetic rehabilitation, taking into account changes in the parameter of biological width of the tooth and aesthetic criteria.